-3x-5y=-17

Y=3x+6

y=4x

y=4x

You have here two equations

equation 1 >>> 3x+y = 6

equation 2 >>> -8-2x-y=6

Taking equation 1 >>> 3x+y = 6

>>> y = 6-3x -- equation 3

put the value of y in equation 2

>>> -8-2x-(6-3x)=6

>>> -8-2x-6+3x=6

>>> -14+x=6

>>> x=6+14

>>> x=20

now put the value of x in equation 3.

Equation 3 >>> y=6-3x

y = 6-3 (20)

y = -54

equation 1 >>> 3x+y = 6

equation 2 >>> -8-2x-y=6

Taking equation 1 >>> 3x+y = 6

>>> y = 6-3x -- equation 3

put the value of y in equation 2

>>> -8-2x-(6-3x)=6

>>> -8-2x-6+3x=6

>>> -14+x=6

>>> x=6+14

>>> x=20

now put the value of x in equation 3.

Equation 3 >>> y=6-3x

y = 6-3 (20)

y = -54